Knowledge-Based Risk Management Model: Application in Energy Infrastructure Projects - Cavaco, Ednilson; Muniz Junior, Jorge (Brazilian Journal of Operations & Production Management, 2020)
Goal: This paper adapted the Knowledge Risk Management model to a Brazilian project-based organization (Alpha Company), which projects and produces hydropower stations. Design / Methodology / Approach: The Alpha Company study is supported by an exploratory fieldwork, which link theoretical and empirical perspectives based on qualitative data analysis from Alpha company expert interviews about risk and knowledge. Alpha Company is a Brazilian manufacturer of equipment for hydropower stations. The experts interviewed represent a broad spectrum of experience in complex projects that assess 24 projects. Results: The application of Knowledge-based Risk Management model and may support project-oriented organizations to mitigate issues related to project management. Limitations of the investigation: The paper is limited to the judgment of specialists involved in the project of hydroelectric plants and indicates as future studies new applications to other sectors and products. Practical implications: Alpha Company study provides a practical guidelines to support possible strategic change to issue previously planned through the project tasks, and support managers to plan how to mitigate risks related to project issues. Originality / Value: This paper proposes an assessment guidelines based on technical knowledge issues to mitigate risks to achieve project. The paper answers to research opportunities raised on Knowledge and risk management literature, such as a) evaluate project risk analysis in different production contexts; b) apply knowledge-based techniques to support risk evaluation; c) model risk identification, d) update the Massingham’ KMR model to project-based organizations.